Den finske folkeskole er med PISA 2009 fortsat blandt verdens bedste – hvad er det, der virker? - Andersen, Frans Ørsted (Politik, 2011)
The article compares Denmark and Finland in order to understand the differences between the relative successes of their school systems. In OECD’s PISA studies, Finnish students repeatedly achieve the highest Nordic scores in reading, science and math, while Danish students score lower. Even though Denmark has one of the world’s most expensive educational systems, the Finnish school system is the World’s best both in terms of quality and equity. The difference between the two national systems mainly rests with differences in how much they are able to raise the level of the 25 percent weakest learners. There is a number of classroom related reasons why the Finnish school system produces a better outcome for the weakest learners. The article underlines the need to focus more on good classroom management and better basic teacher training in Denmark. It also suggests the need for increased knowledge about inclusive classroom practices and the use of teaching assistants.